2016
DOI: 10.1136/jclinpath-2016-203629
|View full text |Cite
|
Sign up to set email alerts
|

Gene of the month:Axl

Abstract: The interaction between Axl receptor tyrosine kinase and its main ligand Gas6 has been implicated in the progression of a wide number of malignancies. More recently, overexpression of Axl has emerged as a key molecular determinant underlying the development of acquired resistance to targeted anticancer agents. The activation of Axl is overexpression-dependent and controls a number of hallmarks of cancer progression including proliferation, migration, resistance to apoptosis and survival through a complex netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 87 publications
(107 reference statements)
0
39
0
Order By: Relevance
“…AXL (previously known as UFO ), is a member of the TMA ( TYRO3 , MER , and AXL ) receptor tyrosine kinase family and has important roles in various cancer processes [reviewed in ref. 41]. AXL amplification has been identified in colorectal cancer 42 Moreover, AXL overexpression has been observed in many solid and hematopoietic malignancies, including Ewing sarcoma tumor tissues 43 and sarcoma cell lines 44 .…”
Section: Discussionmentioning
confidence: 99%
“…AXL (previously known as UFO ), is a member of the TMA ( TYRO3 , MER , and AXL ) receptor tyrosine kinase family and has important roles in various cancer processes [reviewed in ref. 41]. AXL amplification has been identified in colorectal cancer 42 Moreover, AXL overexpression has been observed in many solid and hematopoietic malignancies, including Ewing sarcoma tumor tissues 43 and sarcoma cell lines 44 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous report indicated that the increasing overexpression of AXL was associated with Barrett's carcinogenesis, and could be used as an adverse prognostic marker in EAC (Hector et al, 2010). The increasing knowledge on the role of AXL in regulating several aspects of cancer has justified a growing interest in the development and clinical testing of AXL inhibitors for targeted therapies (reviewed in Brown et al, 2016;Gay et al, 2017;Levin et al, 2016). An early study demonstrated that AXL mediates the acquired resistance to EGFR-targeted therapy in lung cancer (Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Our report, represents the first association of AXL positivity by immunohistochemistry with reduced survival in patients with mRCC treated with sunitinib. AXL has been suggested to promote both intrinsic and acquired resistance to different treatments, from chemotherapy to molecular targets [15]. In RCC xenograft models upregulation of AXL and MET showed resistance to longterm sunitinib therapy, as well as resensitisation to sunitinib after AXL and MET inhibition via treatment with the TKI cabozantinib [34].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkable efforts are being made to identify biomarkers that may predict response to select and treat more effectively patients with metastatic RCC (mRCC) [14]. AXL, a gene that encodes a receptor tyrosine kinase, is involved with a wide variety of cancerous hallmarks such as proliferation, survival, evasion from apoptosis, enhanced angiogenesis, and invasiveness [15,16]. Recently, AXL have been suggested as a biomarker of poor prognosis and a potential target for different types of cancers [17,18], including RCC [19,20].…”
Section: Introductionmentioning
confidence: 99%